1984
DOI: 10.1016/0014-5793(84)80216-1
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation site sequence of smooth muscle myosin light chain (Mr = 20 000)

Abstract: The ammo terminal sequence of the myosin light cham (Mr = 20 000) Isolated from chicken gizzards was found to be acetyl-Ser-Ser-Lys-Ag-Ala-Lys-Ala-Lys-Thr-Thr-Lys-Lys-Arg-Pro-Gln-Arg-Ala-Thr-Ser(P)-Asn-Val-Phe. This sequence assignment differs from that reported by Msuta et al. [(1981) European J. Biochem. 117, 4171 in the order of the tryptic peptides. The revised amino acid sequence exhibits greater homology with the phosphorylation site sequences of the regulatory light chains from cardiac and skeletal mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 15 publications
2
37
0
Order By: Relevance
“…1). All MRLCs were highly homologous with each other, and showed more than 90% amino acid identity to that from chicken smooth muscle (Pearson et al, 1984). Moreover, the phosphorylation sites of MRLC by MLCK were well conserved among these three MRLC isoforms (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…1). All MRLCs were highly homologous with each other, and showed more than 90% amino acid identity to that from chicken smooth muscle (Pearson et al, 1984). Moreover, the phosphorylation sites of MRLC by MLCK were well conserved among these three MRLC isoforms (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…MLCK can also phosphorylate Thr18 of rMLC, but this occurs at a 1,000-fold lower rate. MLCK does not phosphorylate other sites of rMLC, the heavy chain, or the essential light chain (2,19). Consequently, the rate of 32 P release from this phosphorylated myosin only comes from the rMLC, and therefore represents the specific MLCP activity.…”
Section: Protein Phosphatase and Kinase Activity Assaymentioning
confidence: 99%
“…We obtained further evidence that Mbs acts through Sqh by looking at the effects of sqh transgenes with phosphorylation site mutations on the Mbs mutant phenotype. Previous biochemical and genetic studies have shown that serine 21 and threonine 20 are the conserved primary and secondary phosphorylation sites, respectively (Pearson et al, 1984; a The number of nonbalancer flies reaching pupation or adulthood is shown over the total number of flies at that stage. Survival is shown as a percentage of the expected number of nonbalancer flies in parentheses.…”
Section: Mbs Mediates Its Effects On the Eye Through Sqh Dephosphorylmentioning
confidence: 99%